1992
DOI: 10.1002/mus.880150204
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue‐related changes in motor unit action potentials of adult cats

Abstract: The purpose of this study was to quantify the changes in motor-unit action potentials (MUAP) and force during a standard motor-unit fatigue test. MUAP waveforms were characterized by the measurement of amplitude, duration, area, and shape (as reflected in a coefficient of proportionality). Fatigue-resistant motor units exhibited small, but statistically significant, changes in MUAP amplitude and area during the fatigue test, whereas fatigable motor units displayed variable changes in MUAP amplitude, duration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 24 publications
(4 reference statements)
6
43
0
Order By: Relevance
“…These results also show that excitation of the sarcolemma and transmission across the neuromuscular junctions was effective and changes in these processes cannot explain the force loss. Similar conclusions have been reached in studies of single cat and rat motor units (Burke et al 1973;Celichowski et al 1991;Enoka et al 1992;Hamm et al 1989;Sandercock et al 1985), where it has been suggested that force loss relates to changes in phosphate metabolism, intercellular Ca 2ϩ handling and altered cross-bridge kinetics (Edman 1995;Westerblad and Allen 1991;Westerblad et al 1998).…”
Section: Changes In Unit Emg With Fatiguesupporting
confidence: 67%
See 2 more Smart Citations
“…These results also show that excitation of the sarcolemma and transmission across the neuromuscular junctions was effective and changes in these processes cannot explain the force loss. Similar conclusions have been reached in studies of single cat and rat motor units (Burke et al 1973;Celichowski et al 1991;Enoka et al 1992;Hamm et al 1989;Sandercock et al 1985), where it has been suggested that force loss relates to changes in phosphate metabolism, intercellular Ca 2ϩ handling and altered cross-bridge kinetics (Edman 1995;Westerblad and Allen 1991;Westerblad et al 1998).…”
Section: Changes In Unit Emg With Fatiguesupporting
confidence: 67%
“…However, for thenar units, there was usually an increase in the amplitude of the first EMG potential in each train of stimuli (Fig. 6A), whereas more variable amplitude effects have been observed in cat units exposed to the same fatigue protocol (Enoka et al 1992;Sandercock et al 1985). These results may reflect differences in relative contraction intensity.…”
Section: Changes In Unit Emg With Fatiguementioning
confidence: 88%
See 1 more Smart Citation
“…Application of sag and fatigue index according to [2,4] did not enable reliable classification of fast fatiguing, fatigue intermediate and fatigue resistant motor units in our rat EDLs. We noted that the motor unit characteristics in our research varied considerably within a category.…”
Section: Discussionmentioning
confidence: 75%
“…Fatigue itself is normally quantified with the mechanical behavior, but comes to expression in the electrical signals as well. For action potentials of different types of motor units the time characteristics have been followed during fatigue in animal experiments [ 1,2,3,4]. In human recordings a lot of attention has been given to the changes in the frequency spectra of the electromyogram [e.g.…”
Section: Introductionmentioning
confidence: 99%